Analisis Indeks Kepuasan Masyarakat Pada Layanan Sirkulasi Perpustakaan di Kementerian Desa, Pembangunan Daerah Tertinggal dan Transmigrasi - Matulessy, Stella Maria; Noviyanti (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
Library circulation services are essential to carry out a satisfaction survey to determine the level of satisfaction from the community's point of view to improve and develop services in the future. The problems found in the library circulation service of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration (Kemendesa PDTT) are that they have not implemented the Community Satisfaction Index (IKM), the system has not been computerized, the lack of utilization of complaints, suggestions, and input. Therefore, the purpose of this study is to describe and analyze the results of the Community Satisfaction Index on library circulation services at Kemendesa PDTT. The type of research used is quantitative with a descriptive method using Community Satisfaction Index measurements by the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 concernin guidelines for Compiling Public Satisfaction Surveys in Public Service Delivery Units. Sampling technique using Accidental Sampling with a total sample of 73 respondent. Data collection techniques include questionnaires, interviews, observation, and documentation. Data analysis techniques use tabulation, data verification, IKM analysis, and conclusion. The results showed that the Community Satisfaction Index in the Kemendesa PDTT library was included in the "GOOD" category with a value of 81.82. The element that has the highest score is cost/tariff which is worth 100.00 and the element that has the lowest score is complaint, suggestion, and input which is worth 77.05.